HUBUNGAN WORD OF MOUTH TERHADAP BRAND IMAGE, BRAND LOYALTY, BRAND PREFERENCE DAN BRAND LEADERSHIP PELANGAN MEREK MINISO DI JAKARTA BARAT - IRMA SATYA INDRIYANTI; KRISTIN NATALIA (Media Bisnis, 2020)
The purpose of this study was to determine the relationship of word of mouth with brand image, brand loyalty, brand preference and brand leadership of Miniso customers in West Jakarta.The sampling used in this study is nonprobability sampling with a purposive sampling method and will require 116 respondents. Only certain samples that meet the criteria and can be used as samples. For this study, the SPSS program is used to determine the effect of all the independent variables above on the dependent variable. The statistical method in this study is multiple regression. Research shows that word of mouth for brand image, brand loyalty, brand preference and brand leadership of Miniso customers in West Jakarta.